1959
DOI: 10.1139/b59-087
|View full text |Cite
|
Sign up to set email alerts
|

Gene-for-Gene Relationships in Host: Parasite Systems

Abstract: Theoretical consideration of the origin of gene-for-gene relationships led to the conclusion that such relationships, postulated by Flor for the Linum:Melampsora system, should occur as a general rule in host:parasite systems. An ideal gene-for-gene system, with five related host and parasite loci, was designed to illustrate the properties inherent in gene-for-gene systems, and to illustrate a new method of analyzing for these properties. Analyses of published data of the Solanum:Phytopthora and Linum:Melampso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
4

Year Published

1961
1961
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(86 citation statements)
references
References 4 publications
1
81
0
4
Order By: Relevance
“…Testcross refers to the procedure of crossing F1 progeny of these chosen parents with a variety homozygous for the recessive alleles of Mx and M, namely, Hoshangabad (see table 1), used in these studies as the so-called "universal susceptible" (Person, 1959). Assuming genes M' and M can recombine with a frequency p and maintain their specific action after recombination, the expected frequencies of the four testcross progeny phenotypes are set out in table 2.…”
Section: Varietymentioning
confidence: 99%
See 1 more Smart Citation
“…Testcross refers to the procedure of crossing F1 progeny of these chosen parents with a variety homozygous for the recessive alleles of Mx and M, namely, Hoshangabad (see table 1), used in these studies as the so-called "universal susceptible" (Person, 1959). Assuming genes M' and M can recombine with a frequency p and maintain their specific action after recombination, the expected frequencies of the four testcross progeny phenotypes are set out in table 2.…”
Section: Varietymentioning
confidence: 99%
“…Person (1959) suggested that, within the range of rust strains by which Abyssinian and Leona are classified by Flor (1956) to possess one gene each, 2 and P3 respectively, there are, in fact, two and three such genes respectively. However, Lawrence (1977) produced clear evidence inconsistent with such a hypothesis.…”
Section: Discussiorrmentioning
confidence: 99%
“…Host-parasite interactions in cereal rust diseases are governed by a complementary genetic relationship that has been referred to as a gene-for-gene relationship (Person, 1959;Flor, 1971). Although there are differing interpretations of this phenomenon (Person, 1959;Person & Mayo, 1974;Keen, 1982;Ellingboe, 1984), the essential element of a gene-for-gene system is that specific genes in the host and parasite interact to condition a compatible or incompatible relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are differing interpretations of this phenomenon (Person, 1959;Person & Mayo, 1974;Keen, 1982;Ellingboe, 1984), the essential element of a gene-for-gene system is that specific genes in the host and parasite interact to condition a compatible or incompatible relationship. A consequence of genetic specificity is that a host resistance gene is effective only when the corresponding virulence is not prevalent in the rust population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation